Multiloop low bandwidth communication-based power sharing control for microgrids - Erum Pathan; Afarulrazi Abu Bakar; Mubashir Hayat Khan; Muhammad Asad; Haider Arshad (Institute of Advanced Engineering and Science, 2021)
In parallel-connected inverter-based microgrids, the reactive power sharing accuracy can not have satisfactory results effortlessly. Mismatch in feeder impedances of the parallel-connected inverter-based microgrids is a significant cause of inaccurate reactive power-sharing. In voltage source inverters (VSI) based microgrids, especially for the islanded mode of operation, the conventional centralized or decentralized control techniques are not much helpful to control the voltage deviations due to impedance mismatch. Mismatch of the feeder impedance is compensated by the addition of fixed virtual impedance. Whereas, the change in the virtual impedance is compensated by adaptive virtual impedance-based control techniques which are helpful to mitigate power-sharing errors, but in most of the control schemes virtual impedance-based control mechanism needs pre-knowledge of feeder impedance which increases the computational burden. This paper presents a decentralized virtual impedance-based power sharing control. In the proposed control solution to mitigate reactive power sharing errors in distributed generation (DG) units, mismatch of the parallel-connected feeder impedance is equalized by regulating the addition of equivalent impedance to each DG inverter. Proposed control technique offers an independent implementation without any pre-knowledge of the feeder impedance. Hence, the implementation of the control scheme is a straightforward and computational burden is also reduced. Simulation results show the effectiveness of the control scheme.